STRATEGI KONTEN DIGITAL TIKTOK TAMAN KOPI SEBAGAI MEDIA PEMASARAN DIGITAL: STUDI KASUS AKUN TIKTOK @TAMANKOPI - Adha, Adha Dimas Winata; Saleh, Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the forms of digital content and the content strategy implemented by Taman Kopi through its TikTok account @tamankopi. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation, and documentation. The data analysis refers to the AIDDA model (Attention, Interest, Desire, Decision, Action) to examine the effectiveness of the content strategy in attracting and influencing audiences. The results show that the digital content is dominated by informational, entertainment, trend-based, and ambience visualization content, delivered through a soft-selling approach. The content is adaptive to TikTok trends and emphasizes relatable storytelling. In terms of strategy, the attention and interest stages are considered effective in capturing audience engagement through strong hooks and appealing visuals. The desire stage successfully builds audience interest in the experience offered. However, challenges remain at the decision stage, particularly due to limited information and location factors. At the action stage, the content has been able to encourage audiences to visit, although improvements are still needed in strengthening call-to-action (CTA) elements. Overall, the implemented content strategy is fairly effective but requires further optimization to enhance audience conversion.